AB1001 Management of glucocorticoid-induced osteoporosis in rheumatoid arthritis: the example of the "ric nord de france" cohort. (12th June 2018) - Corli, J.; Baudens, G.; Flipo, R.-M.; Cortet, B.; ,
Abstract : Background: Glucocorticoid-induced osteoporosis (GIOP) is the most common cause of secondary osteoporosis. Patients followed for Rheumatoid Arthritis (RA) are particularly exposed to OP and have a greater risk of fracture, which must be prevented. The newest French guidelines for GIOP management were published in 2014 and it is not known yet how they are applied in real life. Objectives: The objective of our study was to investigate the treatment of glucocorticoid-induced osteoporosis in the Rhumatismes Inflammatoires Chroniques – Nord de France (formerly known as RIC-NPC) network in 2016 for patients with rheumatoid arthritis (RA). Methods: In this observational study, the patients studied were followed in the RIC network for RA from 2004 until June 2016, had at least one bone mineral density (BMD) assessment and glucocorticoid therapy during follow-up. Demographic characteristics of patients, BMD results, fractures and treatments implemented were collected from network data completed during consultations by practitioners. Results: 647 patients were enrolled, including 511 women (79%). The average age of patients was 65.5 years (SD=12) with a mean DAS28 of 3.91 (SD=1.44), mean dose of steroid of 7.6 mg (SD=6.6) and a mean duration of treatment of 49 months (SD=53.7). The average T-score at the first BMD assessment was −0.99 at the spine and −1.03 at the total hip. 298 patients received an anti-osteoporotic treatment (46%). Treated patients were older (p<0.0001), with lower weight (p=0.001) and had a lower T-score at both the spine and the total hip (p<0.0001 for both sites). They most often underwent a prior fracture (p<0.0001), and an initial T-score less than – 1.5 SD (p<0.0001). Conclusions: Our study has the advantage of reflecting the management of GIOP in a "real life" cohort. Almost half of our patients followed for RA who received corticosteroids had received treatment. According to French guidelines the number of patients requiring an anti-osteoporotic treatment should be higher. References: [1] Briot K, Cortet B, Roux C, et al. 2014update of recommendations on the prevention and treatment of glucocorticoid-induced osteoporosis. Joint Bone Spine2014;81:493–501. [2] Kok C, Sambrook PN. Secondary osteoporosis in patients with an osteoporotic fracture. Best Pract Res Clin Rheumatol2009;23:769–79. [3] Wibaux C, Baudens G, Cortet B, et al. Évaluation de la prise en charge de l'ostéoporose cortico-induite chez les patientes du réseau RIC-Nord-Pas-de-Calais. Rev Rhum2007;74:1035. Disclosure of Interest: J. Corli Grant/research support from: Amgen, G. Baudens Grant/research support from: Amgen, R.-M. Flipo: None declared, B. Cortet Grant/research support from: Amgen